Building Organizational Citizenship Behavior among Civil Servants: Job Satisfaction Mediates the Relationship between Self-Efficacy and Emotional Intelligence - Dyan Prastika, Netty; Hardiansyah (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
The growing demands of civil servant (ASN) public service encourage the importance of understanding psychological factors such as self-efficacy and emotional intelligence in shaping organizational citizenship behavior. This study aims to determine how self-efficacy and emotional intelligence can influence OCB through job satisfaction. This study used a quantitative method with a SEM design. The sampling technique used purposive sampling, with 381 participants being civil servants in Samarinda City, Indonesia. Data collection used scales of organizational citizenship behavior, emotional intelligence, job satisfaction, and self-efficacy. The fourth scale is an adaptation. Data analysis in this study used Structural Equation Modeling (SEM) with SmartPLS. This technique was chosen because of its ability to test mediation models. The results showed that self-efficacy and emotional intelligence can significantly influence job satisfaction. Meanwhile, job satisfaction can significantly influence organizational citizenship behavior. Job satisfaction can act as a partial mediator in the influence of self-efficacy and emotional intelligence on organizational citizenship behavior. The novelty of this study lies in its examination of the role of job satisfaction as a psychological mechanism linking self-efficacy and emotional intelligence to organizational citizenship behavior (OCB) within a government bureaucratic setting. Theoretically, these findings enrich the public sector organizational behavior literature by highlighting the importance of individual psychological factors in the formation of OCB. Practically, the results offer recommendations for government agencies regarding human resource policies specifically the development of competency-based training programs focused on emotional intelligence and self-efficacy to enhance job satisfaction and foster sustained OCB among civil servants.